A Parasite’s Paradise: Biotrophic Species Prevail Oomycete Community Composition in Tree Canopies - Jauss, Robin-Tobias; Walden, Susanne; Fiore-Donno, Anna Maria; Schaffer, Stefan; Wolf, Ronny; Feng, Kai; Bonkowski, Michael; Schlegel, Martin (Frontiers in Forests and Global Change, 2021)
Oomycetes (Stramenopiles, protists) are among the most severe plant pathogens, comprising species with a high economic and ecologic impact on forest ecosystems. Their diversity and community structures are well studied in terrestrial habitats, but tree canopies as huge and diverse habitats have been widely neglected. A recent study highlighted distinct oomycete communities in the canopy stratum compared to the ground region of three temperate deciduous trees (Quercus robur, Tilia cordata, Fraxinus excelsior). While the communities from the two strata were distinct when taking oomycete abundances into account, they were rather similar when only OTU presence/absence was considered. It remains however unknown if this homogeneity in the OTU presence also leads to a functional homogenisation among microhabitats within the two strata ground and canopy. In this study, we supplemented functional traits to oomycete communities in the tree microhabitats, which were determined over a time period of two years with a metabarcoding approach. Our results showed that even though most oomycetes occurred in all microhabitats, a strong discrepancy between the strata and correspondingly the distribution of oomycete lifestyles could be observed. This pattern was constant over several seasons. Obligate biotrophic species, exclusively feeding on living host tissue, dominated the canopy region, implying tree canopies to be a hitherto neglected reservoir for parasitic protists. OTUs assigned to the genus Hyaloperonospora – parasites highly specialised on hosts that were not sampled – could be determined in high abundances in the canopy and the surrounding air, challenging the strict host dependencies ruled for some oomycetes. Our findings further contribute to the understanding of oomycete ecosystem functioning in forest ecosystems.